Spare [large type] - Harry, Prince, Duke of Sussex, 1984- (Random House Large Print, 2023)
"It was one of the most searing images of the twentieth century: two young boys, two princes, walking behind their mother's coffin as the world watched in sorrow--and horror. As Diana, Princess of Wales, was laid to rest, billions wondered what the princes must be thinking and feeling--and how their lives would play out from that point on. For Harry, this is that story at last. With its raw, unflinching honesty, Spare is a landmark publication full of insight, revelation, self-examination, and hard-won wisdom about the eternal power of love over grief"--